A study of Bos taurus muscle specific enolase; biochemical characterization, homology modelling and investigation of molecular interaction using molecular docking and dynamics simulations - Sariyer, Emrah; Yakarsonmez, Sinem; Danis, Ozkan; Turgut-Balik, Dilek (ELSEVIER, 2018)
Tropical theileriosis caused by Theileria annulata obligate parasite that infect ruminant animals, including Bos taurus. The disease results massive economic losses in livestock production worldwide. Here we describe cloning, expression and both biochemical and structural characterization of beta enolase from Bos taurus in vitro and in silico. The interconversion of 2-phosphoglycerate to phosphoenolpyruvate was catalyzed by enolase is a metalloenzyme in glycolytic pathway and gluconeogenesis. Enolase from Bos taurus was cloned, expressed and the protein was purified at 95% purity using cobalt column by affinity chromatography. The optimum enzymatic activity was calculated at pH 6.5. For the first time in the literature, the kinetic parameters of the enzyme, Vmax and Km, were measured as 0.1141 mM/min and 0.514 mM, respectively. Besides, Bos taurus enolase 3-dimensional structure was built by homology modelling to be used in silico analyses. The interactions of the enzyme-substrate complex were elucidated by molecular dynamics simulations for 100 ns. These interactions were found to be the same as experimentally determined interactions in yeast. These results would enable further structure based drug design studies with the biochemical characterization of the host organism Bos taurus enolase enzyme in vitro and the elucidation of behavior of enzyme-substrate complex in silico. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Enolase; Purification; Biochemical characterization; Homology modelling; Molecular docking; Molecular dynamics simulations; THEILERIA-ANNULATA; CRYSTAL-STRUCTURE; GENE; CLONING; MECHANISM; ALIGNMENT; COMPLEX; QUALITY; ENZYME; Biochemistry & Molecular Biology; Chemistry; Polymer Science